Response Time and Influencing Factors Among Emergency Nurses in Indonesian Hospital: A Scoping Review of Current Evidence - Ramdani D; Kosasih CE; Emaliyawati E (Journal of Multidisciplinary Healthcare)
Dadan Ramdani,1 Cecep Eli Kosasih,2 Etika Emaliyawati2 1Postgraduate Program of Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Department of Critical Care and Emergency Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Etika Emaliyawati, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia, Email etika@unpad.ac.idBackground: The incidence of mass casualty incidents and severe emergencies such as cerebrovascular and motor vehicle accidents in Indonesia is increasing, leading to an increased burden on emergency services. The current literature on response times and associated factors in Indonesian emergency departments (EDs) is extensive yet lacks comprehensive national and regional analysis.Objective: This study aimed to synthesize existing research on emergency nurse response times in Indonesian hospital settings and identify the factors influencing these times.Methods: This study was guided by the PRISMA-ScR framework. This study systematically searched the PubMed/MEDLINE, CENTRAL/Cochrane, EBSCOhost, and Google Scholar databases for studies published between 2019 and 2024. The included studies focused on empirical measurements of response times, defined as the time from patient arrival to initial treatment, with a particular interest in examining variations across different hospital levels and regions within Indonesia. A thematic analysis was conducted in this study.Results: The review included data from 1628 nurses across 13 provinces, highlighting significant variability in response times. Tertiary hospitals generally show faster response times than secondary hospitals. Key factors influencing response times included the demographic aspects of the nursing staff, work environment conditions, and the level of nurse training and education. Specific barriers such as inadequate infrastructure and cultural differences in healthcare-seeking behaviors also play a role.Conclusion: There is a critical need for targeted improvements in hospital infrastructure and staff training programs to enhance response times across all hospital levels in Indonesia. Future policies should focus on equipping secondary healthcare services to efficiently meet emergency care demands.Keywords: emergency department, emergency care, emergency nurse, healthcare infrastructure, intrahospital, nursing education, response time